2020
DOI: 10.2147/dddt.s228047
|View full text |Cite
|
Sign up to set email alerts
|

<p>Induction of Autophagy by Baicalin Through the AMPK-mTOR Pathway Protects Human Skin Fibroblasts from Ultraviolet B Radiation-Induced Apoptosis</p>

Abstract: These authors contributed equally to this work Background: Baicalin, a natural product isolated from Scutellaria radix, has been reported to exert anti-oxidant and anti-apoptotic effects on skin, but the underlying mechanism remains poorly understood. This study aimed to investigate the possible mechanism of anti-UVB effect of baicalin in human skin fibroblasts. Methods: Cell proliferation was estimated by CCK-8 Kit. Apoptotic incidence was detected by flow cytometry with Annexin V-PE/PI apoptosis detection ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 45 publications
(49 reference statements)
1
11
0
Order By: Relevance
“…The study of HK-2 proximal tubule epithelial cells from the human renal cortex found that Baicalin pretreatments could activate the downstream Nrf2 pathway to inhibit the cytotoxic effects of hydrogen peroxide on HK-2 [ 41 ]. It was reported that the mTOR pathway played an important role in follicular development, and that Baicalin could regulate the mTOR signaling pathway of human skin fibroblasts and lung cancer cells [ 42 ]. Our results showed that Baicalin treatments could affect the mTOR pathway, and its activation or inhibition could affect the actions of Baicalin on the granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…The study of HK-2 proximal tubule epithelial cells from the human renal cortex found that Baicalin pretreatments could activate the downstream Nrf2 pathway to inhibit the cytotoxic effects of hydrogen peroxide on HK-2 [ 41 ]. It was reported that the mTOR pathway played an important role in follicular development, and that Baicalin could regulate the mTOR signaling pathway of human skin fibroblasts and lung cancer cells [ 42 ]. Our results showed that Baicalin treatments could affect the mTOR pathway, and its activation or inhibition could affect the actions of Baicalin on the granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although the specific mechanism is unclear, existing research shows that in terms of either keratinocytes or fibroblasts, UVB exposure can cause autophagy changes in either keratinocytes or fibroblasts ( Chen et al, 2018 ; J. A.; Zhang et al, 2020 ). Inhibited autophagy may accelerate cell aging, and activated autophagy may have powerful anti-aging effect (J.…”
Section: Introductionmentioning
confidence: 99%
“… 84 The stability of the Sestrins (SESN)-2 gene after irradiation stimulated AMPK signaling in MCF-7 cells, and it was initiated in dermal fibroblast cells following baicalin treatment. 85 , 86 However, following irradiation, AMPK expression in MDA-MB-231 cells had various effects, including inhibiting apoptosis, inducing G1 cell cycle arrest, and promoting cell growth. 87 , 88 The contradicting effects of AMPK pathways in different cell lines might be the causal mechanisms that occurred during electron irradiation at 6 MeV in the MCF-7, MDA-MB-231, and NIH/3T3 cells.…”
Section: Resultsmentioning
confidence: 99%